Demand Response in Energy Communities Considering the Share of Photovoltaic Generation from Public Buildings - Faria, Pedro (2019)
This paper has as ambit to promote the importance of the prosumer and the sustainable development of a community's energy systems through the aid of the incorporation of renewable energy sources in the market and the concept demand response. Moreover, it is intended to efficiently use the energy surplus produced by the photovoltaic panels of the prosumers for self-consumption, distributed by the remaining members of the community. It is estimated that participants, through the energy management of the community, will be able to verify reductions in electricity bills, as well as be compensated for their contribution to demand response through remuneration. Thus, the proposed methodology contributes in an efficient and sustainable way to be implemented in a community, promoting the use of renewable energy.